Pengaruh Majelis Zikir Surat Al-Ikhlas Terhadap Tingkah Laku Anak Muda - Rosi, Fauzi Fathur; Sugiarto, Sugiarto (Kartika: Jurnal Studi Keislaman, 2023)
Having a sholeh and sholehah child is a desire of all parents. There are many ways that children can be desirable. One of them is putting children in pesantren. Seeing the behavior of young people today is really very concerning. The promiscuity out there very much tends to be bad. In Kertasada Village, this is one of the assemblies that wants to ground Surat al-Ikhlas and improve the behavior of young people.  The establishment of this assembly was because there was one religious figure who tried to make the young man behave well. This assembly tries to invite young people to always increase worship to Allah SWT. On the basis of the above background, the author conducted research on the influence of the Surat al-Ikhlas remembrance assembly on the behavior of young people using qualitative research methods with the type of field research (Field Research), namely data collection by observation and direct interviews with the congregation. This research is descriptive-analpoint with sociological and phenological approaches then analyzes it with qualitative methods. The results of research conducted on the influence of the Surat al-Ikhlas remembrance assembly on the behavior of young people in Kertasada Village, show that the amaliah activities carried out by the Surat al-Ikhlas remembrance assembly congregation in Kertasada Village have a role and benefits as well as a positive influence in shaping the behavior of young people.